Crystallization Studies of Lithium Borosilicate Glasses (Biological Sciences - PJSIR, 2006)
. Lithium borosilicate ternary system is analogous to the most commercially exploited Na O-B O -SiO sys-2          2    3          2tem. The tendency towards liquid-liquid immiscibility is enhanced when sodium is replaced by lithium, which facili-tates the crystallization process. In the present work, three compositions of lithium borosilicate glasses were  formu-2 2 lated and melted by varying the mol percent ratio of SiO  and Li O. The glasses were subsequently subjected tocrystallization by isothermal heat-treatments at identical temperatures for various specific time durations. The crystal growth was found to be linear and the rate of crystallization was dependent on SiO /Li O ratio. The phases that2       2developed during heat-treatments were identified using XRD